ANALISIS PERANCANGAN BISNIS BASEBALL DAN SOFTBALL HOMERUN BATTING CENTER - Ariff, Gerald (Bina Nusantara University, 2011)
Sports are healthy activities that can refresh the body. Some people consider sports as a hobby to be done every week, while others consider sport to be a more regular part of their lifestyles, an there are even those who make it their profession. The urban population desperately needs these activities to keep their bodies fit and healthy, and have begun making sport part of their lifestyle. This lifestyle is not limited by age or gender but is dominated by the upper middle class population. Baseball and softball are among the types of sports that are done in teams or groups. The sport originated from the United States and is very popular there, Japan, and Chile. Baseball and softball are sports that are not yet very popular in Indonesia, compared with soccer, badminton, and volleyball. Even so, Indonesia’s baseball and softball teams have had achievements such as winning the Asian division 2 cup in 2001 and winning in the Asia - Pacific region in 2006. This business model emphasizes the creation and introduction of trends to improve baseball and softball’s sporting exposure in Indonesian society with a ‘batting center’ format that is simple and practical, equipped with 24- hour café facilities as a place to gather, relax, and chat. The design of the business model is through two core phases, namely the business concept and final design as a whole. The business concept is then developed with more detail into the business plan and final design of the prototype.